Factors Affecting Fencers’ Variance in Level Using All Swords - Mahdi, Abdalhadi Hameed; Hussein, Ali Kamal; Znad, Bashar Mohammed (Journal of Physical Education, 2021)
The research aimed at identifying factors affecting the level of fencers in the three known weapons as well as identifying the order of these factors according to the percentage of each factor. The researchers used the descriptive method on (60) fencers who represent the three weapons based on a questionnaire made of five axes and six questions for each axe. The results of the questionnaire showed that central federation duties comes first, technical issues comes next, financial aspects third, external factors forth, and social factors comes last. The data was collected and treated using proper statistical operations to come up with the conclusions and recommendations.